Cell Membrane Camouflaged Hollow Prussian Blue Nanoparticles for Synergistic Photothermal‐/Chemotherapy of Cancer. (7th February 2017) - Chen, Wansong; Zeng, Ke; Liu, Hong; Ouyang, Jiang; Wang, Liqiang; Liu, Ying; Wang, Hao; Deng, Liu; Liu, You‐Nian
Abstract : Nanodrug‐based cancer therapy has been actively developed in the past decades. The main challenges faced by nanodrugs include poor drug loading capacity, rapid clearance from blood circulation, and low antitumor efficiency with high risk of recurrence. In this work, red blood cell (RBC) membrane camouflaged hollow mesoporous Prussian blue nanoparticles (HMPB@RBC NPs) are fabricated for combination therapy of cancer. The stability, immune evading capacity, and blood retention time of HMPB@RBC NPs are significantly enhanced compared with those of bare HMPB NPs. Doxorubicin (DOX), as a model drug is encapsulated within HMPB@RBC NPs with loading capacity up to 130% in weight. In addition, DOX loaded HMPB@RBC NPs show pH‐/photoresponsive release. The in vivo studies demonstrate the outstanding performance of DOX@HMPB@RBC NPs in synergistic photothermal‐/chemotherapy of cancer. Abstract : Red blood cell (RBC) membrane camouflaged hollow mesoporous Prussian blue nanoparticles (HMPB@RBC NPs) are fabricated. With RBC membrane cloaking technique, the stability, immune evading, and blood retention time of HMPB@RBC NPs are significantly increased. Doxorubicin loaded HMPB@RBC NPs show pH‐/photoresponsive release properties. The in vivo studies demonstrate that HMPB@RBC NP is a stealthy system for synergistic photothermal‐/chemotherapy of cancer.